Pengantar Pendidikan Agama Islam Pada Siswa Sekolah Dasar - Ahmad Taufik; Puspitasari, Novi (STAI AL-AMIN, 2024)
This article aims to disclose how to overcome various kinds of associating from Islamic religious education at the elementary school level. Supposedly if the development of growing up elementary school-age children find its own characteristics, the fundamental can be the thinking power of elementary school-age children will develop in the bond spread gradually. It needs to be understood when obtaining the facts will be exactly the success of the scale of adjustment of the goals of the world of education. The research is presented through a descriptive qualitative approach coverage of the library study method (library reseacrh). The results show that the learning system of Islamic religious education in elementary school is quite unique, if in the previous period the thinking power of children was still imaginative and egocentric then at this time the child's thinking power has developed towards concrete thinking, rational or objective patterns. The scope of Islamic religious education studies is the Qur'an, creed, morals, fiqh / worship, and the history of Islamic culture. The method of education that can be applied refers to the Qur'anic method where this dish is the amstal method, the qishah method, the ibrah mauidzah method, the hiwar jadali method, the uswah hasanah method, and the targhib tarhib method. Meanwhile, Islamic Religious Education can be carried out verbally or non-verbally, written or non-written which is aimed precisely at connecting measurements from the analysis of intellectual competence, social competence functions, the fundamental things of complex spiritual competence. It is this, the capacity of Islamic religious education is expected to produce humans who are always coordinated in order to perfect faith, piety, and morals, and actively build Islamic civilization.